Platinum nanoparticles as pH sensor for intelligent packaging - Martins, A. J. (2012)
Pt nanoparticles were produced by reverse micelle templating using DTAB. The resulting nanoparticles showes sizes between 250nm and 500nm and formed clusters. Thioglycolic acid (TGA) was covalently attached to the nanoparticle surface as a stabilizer and as. The Pt nanoparticles were dispersed in water and the dependence of its absorvance on the pH of the solution was studied. The spectra showed surface plamon absorption band at 280nm and also red shifted bands that were attributed to clusters of nanoparticles. It was found that the fraction of cluster population depends on the pH of the aqueous solution and that the response of the Pt nanoparticles to pH variations has a memory effect (hysteresis). The possibility of using these Pt nanoparticles in smart labels for food packaging is outlined.